Resiliensi Remaja Pasca Bencana Erupsi Merapi Tahun 2010 - Setiyawan, Nanang; , Setiyo Purwanto, S.Psi.,M.Si, Psi (2016)
The eruption of Mount Merapi five years ago still left heartsick for many sides. The objective of this research was to understand and describe the efforts of resilience in the teenagers after the eruption of Merapi. The amount of subject of this research was 4 teenagers of Mount Merapi slope residents with characteristics as follows: Teenagers under 18 - 21 years who lived in the slope area of Mount Merapi, they were the residents of Balerante village, Kemalang sub district. Teenagers who underwent a deep trauma due to the disaster of Merapi eruption. The results of this research were: there was potency of resilience in the teenagers of victims of Merapi eruption, in which this potency became the power source to resist and try to change the situation. And it could be seen from: the teenagers accepted the situation and condition affected, making efforts from the spiritual aspect, making effort in real actions in the form of rearranging the wheel of the economy, building and maintaining interpersonal relationship with others. Other findings from this research were family factor and factors which were not aware by the teenagers in the past, they were: factor of believing in Allah's power as well as factor of social support from the fellow victims, the government, and volunteers given to the teenagers in the forms of energy, thought, material and skills to help recovery after the eruption of Merapi in 2010.